2018
DOI: 10.1182/bloodadvances.2018017517
|View full text |Cite
|
Sign up to set email alerts
|

A CD123-targeting antibody-drug conjugate, IMGN632, designed to eradicate AML while sparing normal bone marrow cells

Abstract: The outlook for patients with refractory/relapsed acute myeloid leukemia (AML) remains poor, with conventional chemotherapeutic treatments often associated with unacceptable toxicities, including severe infections due to profound myelosuppression. Thus there exists an urgent need for more effective agents to treat AML that confer high therapeutic indices and favorable tolerability profiles. Because of its high expression on leukemic blast and stem cells compared with normal hematopoietic stem cells and progeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(88 citation statements)
references
References 47 publications
1
84
0
Order By: Relevance
“…Novel therapies have been developed in the last decade, some showing temporal success and some showing a brighter tomorrow. 216 AMG330 is a bispecific T-cell engager (BiTE) antibody with specificity for CD3 and CD33. This Mab is currently in clinical trials to be completed in 2020 for treatment of AML.…”
Section: B-cell Chronic Lymphocytic Leukemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Novel therapies have been developed in the last decade, some showing temporal success and some showing a brighter tomorrow. 216 AMG330 is a bispecific T-cell engager (BiTE) antibody with specificity for CD3 and CD33. This Mab is currently in clinical trials to be completed in 2020 for treatment of AML.…”
Section: B-cell Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…Ongoing clinical trials will be completed in 2021. 216 Talacotuzumab is a humanized monoclonal antibody (IgG1-2k) with specificity to interleukin (IL)-3 receptor subunit-a (CD123, a growth and differentiating receptor). This antibody induces ADCC both in vitro and in animal models.…”
Section: B-cell Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…CD123, the alpha subunit of the IL-3 receptor, is overexpressed in multiple hematologic malignancies, including AML, ALL, and blastic plasmacytoid dendritic cell neoplasm (BPDCN). Because of its high expression on leukemic blasts as compared with normal hematopoietic stem cells, CD123 has emerged as an attractive candidate for molecularly targeted therapeutics [25]. Tagraxofusp-erzs (Elzonris, Stemline) and IMGN632 (immunogen) are two anti-CD123-directed immunotoxins which have been developed in recent years.…”
Section: Targeting Cd123mentioning
confidence: 99%
“…IMGN632 is comprised of a novel humanized anti-CD123 antibody, G4723A, linked to a unique DNA-alkylating payload of the recently developed IGN (indolinobenzodiazepine pseudodimer) class of cytotoxic compounds [25,29]. Kovtun et al showed that IMGN632 demonstrated potent activity in all AML samples at concentrations well below levels that impacted normal bone marrow progenitors and exhibited robust antitumor activity with a wide therapeutic index in multiple AML xenografts [25].…”
Section: Targeting Cd123mentioning
confidence: 99%
“…It resulted in 600 times more potency in vitro , which makes the PBD dimer an attractive payload for ADCs. There are 13 ADCs [Vadastuximab talirine/SGN-CD33A [27–29],SGN-CD70A [30], SGN-CD19B, SGN-CD123A [31], SGN-CD352A [32], Rovalpituzumab tesirine/Rova-T [33–35], ADCT-301/HuMax-TAC-PBD [36], ADCT-402 [37], MEDI3726/ADC-401, IMGN779 [38], IMGN632 [39], SC-002 and SC-003] with PBD payloads currently being tested in clinical trials. There are two possible reasons that make PBDs the most prominent class of DNA-damaging payloads: (1) PBDs have picomolar activity in vitro and demonstrated therapeutic index in clinic [40].…”
Section: Introductionmentioning
confidence: 99%